Potential effects of allyl isothiocyanate on inhibiting cellular proliferation and inducing apoptotic pathway in human cisplatin-resistant oral cancer cells - Chang, Pei-ying; Tsai, Fuu-jen; Bau, Da-tian; Hsu, Yuan-man; Yang, Jai-sing; Tu, Ming-gene; Chiang, Shang-lun (Journal of the Formosan Medical Association, 2021)
Cisplatin-resistant oral cancer is clinically difficult to manage and the dose-dependent toxicities of cisplatin has been widely concerned. Allyl isothiocyanate (AITC), known as mustard oil, is a plant-derived compound abundant in cruciferous vegetables. It is reported to have anti-cancer potential as a natural dietary chemopreventive compound against a variety of cancers, but the effect of AITC on cisplatin-resistant cancer cells is still little-known. Human CAL27-cisplatin-resistant oral cancer cells (CAR cells) were examined to investigate the antitumor properties of AITC. 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay, IncuCyte™ S3 cell proliferation assay, 4′,6-diamidino-2-phenylindole (DAPI) and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining as well as Western blot analysis were deployed. AITC decreased CAR cell viability, induced cell death of CAR cells and inhibited the confluences of cultured CAR cells. When CAR cells were treated with AITC, activation of caspase-3 and caspase-9 by AITC was observed and could be reversed by Z-VAD-fmk (pan-caspase inhibitor). Furthermore, the protein expressions of phosphorylated protein kinase B (p-AKT) and phosphorylated mammalian target of rapamycin (p-mTOR) were suppressed in AITC-treated CAR cells, whereas protein expressions of Bax, cytochrome c, Apaf-1, cleaved caspase-3, and cleaved caspase-9 were upregulated in AITC-treated CAR cells. AITC can inhibit Akt/mTOR proliferation signaling and promote mitochondria-dependent apoptotic pathway through AITC-enhanced activities of caspase-3 and caspase-9 in CAR cells.